“Our Old Friend across the Hill Yonder” : Perceptions of the Enemy in the First World War - Querido, Pedro (2021)
A British soldier named Harry was captured in the Third Battle of Ypres. In August 1917, now a prisoner of war in Germany, he wrote to his wife in a cheerful manner, narrating his latest misadventures. He ended the letter on a reassuring note: “Our friend the enemy have been very good to us up to now, quite like our own men are with the prisoners” (Imperial War Museum 1978). Paul Fussell’s notion of the “gross dichotomizing” between “the enemy” and “we” in the First World War (Fussell 1975: 75) certainly holds true for civilians and eager and yet inexperienced soldiers, but that is challenged by veterans’ remarks such as the one just mentioned and by large-scale events like the famous Christmas Truce. How did the soldier really regard those men on the other side whom it was his duty to kill? In this article, we will analyse a sample of texts which may be deemed representative of the different perceptions of the enemy during the Great War, with a particular focus on wartime poetry and on the veterans’ post-war prose.